Da (im)possibilidade da execução das medidas cautelares determinadas pelo árbitro de emergência no âmbito das arbitragens internacionais - Barbosa, Beatriz Oliveira (2019)
This report is the result of the curricular internship concluded with the purpose of obtaining a Master's degree in Forensic Law and Arbitration, and held at the Civil and Commercial Arbitration Court (CIMA) located in Madrid, Spain. During the period from September 2018 to February 2019, in the scope of the internship mentioned, activities in support of the management of the arbitration proceedings of the secretariat were developed. The granting of prudential jurisdiction by the arbitral court is a recent phenomenon and, consequently, so is the creation of the emergency arbitrator. The emergency arbitration proceeding consists of a faster arbitration procedure, through which the parties can obtain precautionary measures before the arbitration tribunal is established, which, depending on the peculiarities of the particular case, may result in more efficient and economical protective custody. However, despite the massive incorporation of the emergency arbitrator into the regulations of the arbitration institutions, ignorance about the advantages and disadvantages of using this institute when compared to the state judicial process is a reality among professionals in the area. In this context, the main objective of this research is to present to the reader the institute of the emergency arbitrator, discussing its competence to order precautionary measures ante causum as well as on the emergency arbitration procedure itself, and discuss the feasibility of the enforcement of these interim measures in international arbitrations considering the consequences of the provisional nature and urgency inherent in the nature of these measures, the lack of coercive powers of the emergency arbitrators and the legal certainty and stability of the judicial decisions that are essential to the rule of law.